Model Pembaruan Pendidikan Islam di Indonesia - Sabila, Dayana; Albina, Meyniar (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses the efforts of Islamic figures and organizations in modernizing Islamic education in Indonesia. They see that traditional Islamic education is outdated and needs to be adjusted to the times. These modernization efforts include changes in the teaching and learning system, from what was previously individual to more collective and democratic. This study uses a literature study approach to examine how Islamic figures and educational institutions have attempted to overcome the backwardness of Muslims by reforming the education system. Figures such as KH Ahmad Dahlan, KH Hamka, and KH Hasyim Asy'ari became pioneers in this Islamic education modernization movement. Islamic figures and organizations have attempted to change the Islamic education system, which was previously very individual and led by one person (mono leader) into a more collective and democratic system, such as the classical learning system that involves many people.